Impedance spectroscopy of manganese-doped mixed alkali phosphate glasses. (2022) - Jerroudi, M.; Bih, L.; Haily, E.; Saadoune, I.
Highlights: Elaboration of glasses inside the system Na2 O-K2 O-MnO2 -P2 O5 . The electrical parameters including conductivity, activation energy and electrical modulus are determined. Investigation of the electrical responses by impedance spectroscopy. The MAE is confirmed by the above technique in studied glasses. Abstract: Glassy-compositions in the system 49.95[xNa2 O-(1-x)K2 O]-0.1MnO2 -49.95P2 O5 (with x = 0–1 mol%) were elaborated using melt quenching method. The amorphous state of the samples is ensured by the XRD diffraction technique. The electrical properties including dc conductivity, ac conductivity, and electrical modulus were investigated over a large frequency domain at various temperatures. The evolution of the electric conductivity shows a non-linear variation with the composition. It is found that the activation energy is more sensitive to the substitution of the alkali elements and presents a minimum in the intermediate composition (x = 0.5). The non-linearity behavior of the composition dependence of the electrical parameters is a fingerprint of the mixed alkali effect in the glasses under study. The frequency-dependent of the conductivity follows Jonscher's power law and the correlated barrier hopping mechanism (CBH) was appropriate for the conduction process inside the glasses. In order to avoid the polarization effect due to the electrodes, the electrical modulus formalism is applied to the impedance data. The results obtained show that conduction relaxation is a non-Debye type.